Transcultural adaptation and validation of Italian Selfcare diabetic foot questionnaire - Navarro‐Flores, Emmanuel (Int Wound J, 2021)
The Italian Selfcare diabetic foot questionnaire, (SDFQ‐IT) is considered a diabetic foot self‐care evaluation tool with 16 questions for assessing diabetic foot health disorders. To date, SDFQ has been validated in different languages, but an Italian version was lacking. Consequently, the purpose of this study was to translate and validate the Italian version of the SDFQ‐IT (SDFQ‐IT). A suitable method was developed for the translation protocol and cross‐cultural validation from Spanish to Italian. Regarding the total marks from each sub‐scale, agreement degrees, and confidence were analysed using the Cronbach's α and intraclass correlation coefficient (ICC), respectively. In addition, the mean ± SD differences between pre and post‐tests were calculated and completed using the Bland and Altman distribution plots. Excellent agreement between the two versions based on Cronbach's α was demonstrated. Three sub‐scales consisting of knowledge of foot hygiene, the appropriate use of footwear and socks, and podiatric self‐care were added together to obtain the total score. Excellent retest reliability was shown for the total score. Test/retest reliability was excellent for the self‐care domain, and shock and shoe sub‐scales. There were no significant differences among any domain (P > .05). There were no statistically significant differences (P = .000) for the mean ± SDs differences between pre‐and post‐tests (92.9200 ± 12.914) [89.25‐96.59] and 92.9200 ± 13.012 [89.22‐96.62] points, respectively). Bland and Altman plots or clinically pertinent variations were not statistically significantly different. The SDFQ‐IT is considered a strong and valid questionnaire with adequate repeatability in the Italian community.